The Negative Impact of Social Media on Generation Z in Election Activities in 2024 - Mulyadi, Dedi; Nursyakinah, Kintan Berlina; Baidhowi, Nayla Ratu; Hidayat, Cep; Saharani, Tria Rizki; Tricahya, Muhammad Agung; Maswah, Eris Zanatul (Sinergi International Journal of Law, 2024)
Social media has become the main platform for Generation Z to obtain political information and participate in the political process. However, in this context, social media can also bring a number of negative impacts that can affect Generation Z's ability to make rational choices. This research investigates the negative impact of social media on Generation Z in the process of making rational choices in the 2024 general election with the aim of improving the quality of Generation Z's thinking and expanding their rationalisation in making choices and determining leaders who will be influential in the future. The method used in this research is a qualitative method with the nature of a normative juridical approach, which is carried out by examining library materials or secondary data. The results showed that the negative impact of the role of social media on Generation Z greatly influenced Generation Z's rational choice of Presidential and legislative elections in 2024. This is because Generation Z's quality of thinking is vulnerable to the negative impact of social media, making it difficult for Generation Z to make rational choices in elections. This finding has significant implications for the democratic process, given that Generation Z is an important future voter.